Revisiting the rewarding properties and abuse potential of natural compound sinomenine using conditioned place preference (CPP) model in mice / Nur Syamimi Ma’arof ... [et al.] - Ma’arof, Nur Syamimi; Ali, Aida Azlina; Jayasingh Chellammal, Hanish Singh; Zulkifli, Muhammad Harith (Faculty of Pharmacy, 2024)
Sinomenine, derived from Sinomenium acutum, has a chemical structure similar to morphine and shows potential for treating opioid addiction in mice. Despite claims of being nonaddictive, its safety and abuse potential remain underexplored. Conditioned place preference (CPP) approach was used to evaluate sinomenine's rewarding properties. ICR mice were divided into five groups, receiving either saline, morphine (8 mg/kg), or sinomenine (50, 100, or 200 mg/kg) where each group was confined to the drug-paired compartments during conditioning phase. Alternately, mice received saline when confined in the saline-paired compartment. During pre-conditioning and post-conditioning phases, the time spent in the drug-paired compartment, the number of entries to the drug-paired compartment, and rearing behaviours to assess the rewarding properties. Mice conditioned with morphine showed a significant increase in time spent in the drug-paired compartment from pre-conditioning to post-conditioning, but no significant changes in the number of entries and rearing behaviours. For saline and all sinomenine groups, there were no significant differences in the time spent, number of entries, and rearing behaviours except for sinomenine 200 mg/kg group, which showed a significant increase in rearing behaviours indicating an increase in exploratory behaviours. This study suggests that sinomenine, at various doses, is less likely to produce rewarding effects, indicating low abuse potential. The observed increase in exploratory behaviours during post-conditioning with sinomenine 200 mg/kg warrants further investigation.